Student behavior and performance in alternative assessment for selected concepts in biology - Sebastian, Ma. Dulcelina O. (2008)
This is a study on how students do alternative assessment in Biology. A research class of 39 fourth year high school students aged 15-17 years old from a science high school in Metro Manila was involved in the study. Descriptive analysis was employed to determine their behavior. Students' level of performance in a task was examined and evaluated using a Task Sheet and an accompanying scoring rubric. Based on the data, students who perform the alternative tasks most frequently demonstrate on-task behaviors, engage in interactions with other students in the group, demonstrate other personal reactions and off-task behaviors in lesser frequency, and their interaction with the teacher although occuring very seldom is of substance and task-oriented. Students possess a strong positive attitude towards alternative assessment, which varies depending on the specific assessment task they perform.